2014
DOI: 10.1002/jsfa.6988
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy, a summary of eight cases in the UK criminal and civil courts: effective last resort for vulnerable consumers?

Abstract: Food allergy has a forensic context. The authors describe eight cases in the UK courts involving fatalities, personal injury or criminal non-compliance with food law from mainly 'grey' literature sources. The potentially severe consequences for people with food allergy of contraventions of labelling law have led to enforcement action up to criminal prosecution for what might otherwise be regarded as 'trivial' non-compliance. The authors suggest there should be central collation of such cases. Non-compliances s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…8 However, cross-contamination of allergens into unlabeled foods may still occur in shared production facilities, on shared equipment, or along the supply chain. 9 In one European study, peanut was found in 25% of cookies and 43% of chocolate labeled with the precautionary phrase ‘may contain.’ More worrying was that 11% of cookies and 25% of chocolate without advisory labeling tested positive for peanut. 10 In another example, the US Food and Drug Administration found evidence of milk in 75% of chocolate products with advisory labeling and evidence of milk even in products without advisory labeling or specifically with dairy-free claims.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, cross-contamination of allergens into unlabeled foods may still occur in shared production facilities, on shared equipment, or along the supply chain. 9 In one European study, peanut was found in 25% of cookies and 43% of chocolate labeled with the precautionary phrase ‘may contain.’ More worrying was that 11% of cookies and 25% of chocolate without advisory labeling tested positive for peanut. 10 In another example, the US Food and Drug Administration found evidence of milk in 75% of chocolate products with advisory labeling and evidence of milk even in products without advisory labeling or specifically with dairy-free claims.…”
Section: Introductionmentioning
confidence: 99%
“…Leavitt (2011: 968) and Brewer (2016: 310) discuss various legal theories in which a restaurant could be found liable to customers for injuries arising from a failure to warn about a food allergen or providing incorrect information regarding the presence of a food allergen in a menu item. Unfortunately, this is not an uncommon occurrence (Gowland and Walker, 2014: 1981–1982; Kronenberg, 2012: 118; Leavitt, 2011: 970). Clinical records suggest that foods sold in restaurants and other non-pre-packaged formats present a greater risk of fatal and near-fatal allergic reactions relative to pre-packaged foods (Commission of the European Communities, 2008: 51).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Incidents are identified by various means, including by the companies' own checks, consumer reports, and enforcement surveillance. Compensation in civil law for loss or damage caused by an allergic reaction to a food supplied is a foreseeable risk for food businesses (26).…”
Section: Management Of Incidentsmentioning
confidence: 99%